Penerapan User Acceptance Testing (UAT) dalam Evaluasi Sistem Informasi Pencarian & Pemesanan Rumah Kost menggunakan Progressive Web App Berbasis Geospasial - Nurfadillah Nurfadillah; Reza Maulana; Syahbudin Syahbudin (Switch : Jurnal Sains dan Teknologi Informasi, 2026)
The search and booking of boarding houses (kost) remain a significant challenge for newcomers in campus areas, particularly in Kelurahan Samata, home to UIN Alauddin Makassar, which admits approximately 15,000 new students annually. Many of these students come from outside the region and require temporary accommodation near the campus. This issue is primarily caused by limited access to information and the lack of an optimal system to support the search and booking process. Therefore, it is necessary to evaluate the level of user acceptance of the developed system. This study aims to analyze user acceptance of a boarding house search and booking information system in the case of Kelurahan Samata using the User Acceptance Testing (UAT) method. UAT is a testing approach used to determine whether a system meets user requirements, is accepted according to expected standards, and to identify the need for further improvements to ensure its feasibility for use. The UAT was conducted by end users, namely boarding house seekers and property owners/managers, by responding to 10 evaluation indicators: (1) ease of search, (2) time efficiency, (3) booking process, (4) geospatial search features, (5) completeness of information, (6) availability of suitable boarding houses, (7) accuracy of information, (8) ease of payment process, (9) check-in scheduling, and (10) navigation features for directions. The results of the User Acceptance Testing (UAT) indicate that the system achieved an average score of 87.77, suggesting that the system is highly acceptable and significantly facilitates users. These findings demonstrate that the system is well received by users, confirming that it functions effectively and is capable of accommodating all required functionalities.